2014
DOI: 10.1007/s10741-014-9439-6
|View full text |Cite
|
Sign up to set email alerts
|

BNP and NT-proBNP as prognostic markers in persons with chronic stable heart failure

Abstract: Prognosis permits clinicians to separate persons with heart failure (HF) into subgroups based on likely health outcomes. Treatment is partly guided by these likely outcomes. This systematic review explores whether brain natriuretic peptide (BNP) and N-terminal proBNP (NT-proBNP) are independent predictors of prognosis in persons with chronic stable HF. We electronically searched Medline, Embase, AMED, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and CINAHL for Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 99 publications
2
73
0
4
Order By: Relevance
“…Recent clinical studies have been shown that short-term and long-term prognosis among heart failure persons may be reappraised and recalculated using biological marker models demonstrated to be credible in clinical practice and useful predictable tool for physicians [78][79][80][81]. Natriuretic peptides, galectin-3 (Gal-3), and high sensitive C-reactive protein (hs-CRP) were positively associated with all-cause and cardiovascular mortality and were discussed useful for estimating prognosis in persons with different cardiovascular diseases [82][83][84][85]. Therefore, a wide spectrum of biomarkers reflected immune status, proinflammatory activation, endothelial function, was tested in predictive models for cardiovascular disease patients [77].…”
Section: Endothelial-derived Microparticles In Heart Failurementioning
confidence: 99%
“…Recent clinical studies have been shown that short-term and long-term prognosis among heart failure persons may be reappraised and recalculated using biological marker models demonstrated to be credible in clinical practice and useful predictable tool for physicians [78][79][80][81]. Natriuretic peptides, galectin-3 (Gal-3), and high sensitive C-reactive protein (hs-CRP) were positively associated with all-cause and cardiovascular mortality and were discussed useful for estimating prognosis in persons with different cardiovascular diseases [82][83][84][85]. Therefore, a wide spectrum of biomarkers reflected immune status, proinflammatory activation, endothelial function, was tested in predictive models for cardiovascular disease patients [77].…”
Section: Endothelial-derived Microparticles In Heart Failurementioning
confidence: 99%
“…Elevated levels of NT-proBNP are associated with adverse cardiovascular (CV) outcomes in the setting of acute and chronic heart failure (HF) and stable coronary artery disease (CAD) [5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…NT-proBNP is a marker of systolic and diastolic dysfunction and a strong predictor of mortality in heart failure patients [18,19]. Markers of LV overload such as NT-proBNP have already been shown to decrease after successful AVR [20].…”
Section: Discussionmentioning
confidence: 99%